Meningkatkan Hasil Belajar PAK Pada Materi Manusia Makhluk Otonom Melalui PBL Berbantuan E-LKPD Kelas X SMAN 1 Palangkaraya - Ernita Fransiska (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
. Education problems in Indonesia cover various aspects that influence the quality and effectiveness of learning. Some of these problems include irrelevant curricula, variations in the quality of teacher teaching, shortage of qualified teachers, inadequate educational facilities, less interactive learning methods, emphasis on standardized tests, limited technology in learning, unequal online access, and inadequate parental involvement. limited. Improvement efforts have been made through curriculum development, teacher training, facility improvements, use of interactive learning methods, holistic assessment, technology integration, and overcoming inequalities in access. The government has innovated by introducing the Independent Curriculum as an educational approach that is more contextual, interactive and student-centered. However, research shows that student learning outcomes in the material "Humans are Autonomous Creatures" with the topic "Being Critical of Mass Media, Ideology and Lifestyle in Catholic Religious Education" are still not optimal. To overcome this problem, this research implements the Problem Based Learning (PBL) model using Student Worksheets (LKPD) as a tool. The objectives of this research are (1) To find out how to increase the dimensions of critical thinking through the PBL model for phase E class students. X in the material "Be Critical and Responsible for the Mass Media, Ideology, and Lifestyle Today" at SMAN 1 Palangkaraya. Answers to Mass Media, Ideology and Current Lifestyles" at SMAN 1 Palangkaraya. (3) Knowing the increase in learning outcomes that are influenced by critical thinking skills through the PBL model for students in phase E class 1 Palangkaraya. The type of research used is qualitative classroom action research with a descriptive approach. Data is collected through tests and observations, and analyzed through data reduction steps, data presentation, and drawing conclusions. The research results show that the application of the Problem Based Learning (PBL) model with the help of E-LKPD is effective in improving learning outcomes and students' critical thinking abilities in autonomous human beings in class X SMAN 1 Palangkaraya.